Functional Trait Variation Among and Within Species and Plant Functional Types in Mountainous Mediterranean Forests - Fyllas, Nikolaos M.; Michelaki, Chrysanthi; Galanidis, Alexandros; Evangelou, Eleftherios; Zaragoza-Castells, Joana; Dimitrakopoulos, Panayiotis G.; Tsadilas, Christos; Arianoutsou, Margarita; Lloyd, Jon (Frontiers in Plant Science, 2020)
Plant structural and biochemical traits are frequently used to characterise the life history of plants. Although some common patterns of trait covariation have been identified, recent studies suggest these patterns of covariation may differ with growing location and/or plant functional type (PFT). Mediterranean forest tree/shrub species are often divided into three PFTs based on their leaf habit and form, being classified as either needleleaf evergreen (Ne), broadleaf evergreen (Be) or broadleaf deciduous (Bd). Working across 61 mountainous Mediterranean forest sites of contrasting climate and soil type, we sampled and analysed 626 individuals in order to evaluate differences in key foliage trait covariation as modulated by growing conditions both within and between the Ne, Be and Bd functional types. We found significant differences between PFTs for most traits. When considered across PFTs and by ignoring intraspecific variation, three independent functional dimensions supporting the Leaf-Height-Seed framework were identified. Some traits illustrated a common scaling relationship across and within PFTs, but others scaled differently when considered across PFTs or even within PFTs. For most traits much of the observed variation was attributable to PFT identity and not to growing location, although for some traits there was a strong environmental component and considerable intraspecific and residual variation. Nevertheless, environmental conditions as related to water availability during the dry season and to a smaller extend to soil nutrient status and soil texture, clearly influenced trait values. When compared across species, about half of the trait-environment relationships were species-specific. Our study highlights the importance of the ecological scale within which trait covariation is considered and suggests that at regional to local scales, common trait-by-trait scaling relationships should be treated with caution. PFT definitions by themselves can potentially be an important predictor variable when inferring one trait from another. These finding have important implications for local scale dynamic vegetation models.